Adoption of E-HRM Practices in the IT Industry: With Reference to IT Companies in Bengaluru - Srihari, S.; Kar, Subhasree (International Journal of Psychosocial Rehabilitation, 2024)
The IT industry all over the world is considered the early adopters of IT-based systems in their respective organizations and particularly in their human resources departments. This was not done overnight; rather, it is out of compulsion that the most developed systems in any of the industries are the result of IT companies; hence, it is the responsibility of IT industries to become the pioneers of E-HRM implementation in their respective organizations. This present study is based on the evaluation of the adoption of E-HRM and the effect of the same on the performance of employees working at the middle level of management in the selected IT companies of Bengaluru. The respective sample of the study is 100 respondents. chi square test is used to analyze the results and SPSS Ver. 20.0 is analyzing the results